Retroperitoneoscopic bladder neck closure for continuous urinary incontinence in Fournier's gangrene - Yukiko Doi; Atsuhiko Ochi; Yuma Okamoto; Akira Komiya; Hiroshi Kuji; Koichiro Suzuki; Naoki Shiga; Hirokazu Abe (IJU Case Reports)
Introduction A retroperitoneoscopic procedure for bladder neck closure has not yet been described. Case presentation Case 1 was a 56‐year‐old man who underwent clean intermittent catheterization for spastic paraplegia due to a thoracic spinal cord injury 37 years prior. Case 2 was an 80‐year‐old bedridden woman who underwent urethral catheterization after a femoral fracture and brain infarction 3 years prior. Both patients presented with Fournier's gangrene, and the urogenital region, including the necrotic urethra, was debrided. Although a permanent suprapubic catheter was established, postoperative wound healing was poor owing to continuous urine leakage from the urethral stump. Therefore, we performed retroperitoneoscopic bladder neck closure, and the urinary incontinence was completely resolved. Conclusion Retroperitoneoscopic bladder neck closure is a feasible and less invasive procedure for treating continuous urinary incontinence from the urethral stump in patients with Fournier's gangrene after surgical debridement and having a permanent suprapubic catheter.